Positive electrode active material, method for preparing same, positive electrode, and rechargeable lithium battery

By forming aluminum and yttrium coatings on the positive electrode active substance of lithium nickel manganese and aluminum composite oxide, the problems of cobalt shortage and high cost are solved, and the effects of high capacity, long cycle life and low gas generation of lithium batteries are achieved. .

CN119133376APending Publication Date: 2024-12-13SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410744222.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-12
Filing Date
2024-06-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The shortage of cobalt in the positive electrode active substance of existing lithium batteries and high costs leads to problems such as reduced structural stability, short cycle life and increased gas production under high voltage and high temperature conditions.

Method used

Li-nickel, manganese, aluminum, aluminum composite oxides are used as positive electrode active substances, and a coating of aluminum and yttrium is formed on its surface. Prepared by heat treatment, the nickel content is greater than 60 mol%, and the aluminum and yttrium content is between 0.1 mol% and 2 mol% and Between 0.05mol% and 1mol%, to improve structural stability and cycle life.

Benefits of technology

The positive electrode active substance with high capacity, long cycle life and low gas production volume under high voltage and high temperature conditions is realized, reducing production costs and ensuring the economic feasibility and efficient performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133376A_ABST
    Figure CN119133376A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode active material, a method of preparing the same, a positive electrode, and a rechargeable lithium battery. The positive electrode active material includes: a core particle including a lithium nickel manganese aluminum-based composite oxide; and a coating layer disposed on a surface of the core particle and containing aluminum and yttrium, in which a nickel content (e.g., an amount) in the core particle is greater than or equal to about 60 mol% based on 100 mol% of the total metal other than lithium in the positive electrode active material, and an aluminum content (e.g., an amount) in the coating layer is greater than or equal to about 60 mol% based on 100 mol% of the total metal other than lithium in the positive electrode active material, each based on 100 mol% of the total metal other than lithium in the positive electrode active material. The coating has an yttrium content (e.g., an amount) of about 0.1 mol% to about 2 mol%, and the coating has an yttrium content (e.g., an amount) of about 0.05 mol% to about 1 mol%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material, a preparation method thereof, a positive electrode including the positive electrode active material, and a rechargeable lithium battery including the positive electrode. Background Art

[0002] Portable information devices (such as cellular phones, laptop computers, smart phones, etc.) and / or electric vehicles have used rechargeable lithium batteries with relatively high energy density and easy to carry as driving power sources. Recently, research on using rechargeable lithium batteries with relatively high energy density as driving power sources for hybrid vehicles and / or electric vehicles, or as power storage power sources for home power storage units and / or power walls has been actively conducted.

[0003] Various positive electrode active materials have been studied to realize rechargeable lithium batteries suitable for the purposes. Among them, lithium nickel oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides and lithium cobalt oxides are mainly used as positive electrode active materials. However, despite the recent increase in demand for relatively large, relatively high capacity or relatively high energy density rechargeable lithium batteries, it is expected that the supply of positive electrode active materials containing rare metal cobalt will be in short supply (severe shortage). For example, because cobalt is expensive and the remaining reserves are lacking (for example, the availability is reduced), it is necessary to develop a positive electrode active material that excludes (for example, does not include or does not contain) cobalt or uses cobalt in a reduced amount. Summary of the invention

[0004] Aspects according to some embodiments relate to a positive electrode active material, a method for preparing a positive electrode active material, a positive electrode including the positive electrode active material, and a rechargeable lithium battery including the positive electrode, wherein the positive electrode active material includes a lithium nickel manganese aluminum type composite oxide to ensure economic feasibility, high capacity and long cycle life characteristics, and exhibits improved high voltage characteristics and high temperature characteristics.

[0005] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the presented embodiments of the disclosure.

[0006] In one or more embodiments, the positive electrode active material includes: a core particle (e.g., one core particle) including a lithium nickel manganese aluminum composite oxide; and a coating located on the surface of the core particle (e.g., one core particle) and containing aluminum and yttrium, wherein the nickel content (e.g., nickel in the core particle) is greater than or equal to about 60 mol% based on 100 mol% of the total metals other than lithium in the positive electrode active material, and the aluminum content (e.g., amount) of the coating is about 0.1 mol% to about 2 mol%, and the yttrium content (e.g., amount) of the coating is about 0.05 mol% to about 1 mol%, each based on 100 mol% of the total metals other than lithium in the positive electrode active material.

[0007] In one or more embodiments, a method for preparing a positive electrode active material includes mixing a nickel-manganese-aluminum composite hydroxide and a lithium raw material and performing a first heat treatment to obtain a lithium-nickel-manganese-aluminum composite oxide, and adding the lithium-nickel-manganese composite oxide to a solution of an aluminum raw material and a yttrium raw material mixed in an aqueous solvent, followed by mixing, drying and performing a second heat treatment to obtain a positive electrode active material, wherein the nickel content (e.g., amount) in the nickel-manganese-aluminum composite hydroxide is greater than or equal to about 60 mol% based on 100 mol% of the total metals in the nickel-manganese-aluminum composite hydroxide, the aluminum content (e.g., amount) from the aluminum raw material is about 0.1 mol% to about 2 mol% based on 100 mol% of the total metals other than lithium in the positive electrode active material, and the yttrium content (e.g., amount) from the yttrium raw material is about 0.05 mol% to about 1 mol% based on 100 mol% of the total metals other than lithium in the positive electrode active material.

[0008] In one or more embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material.

[0009] In one or more embodiments, a rechargeable lithium battery includes the aforementioned positive electrode, negative electrode, and electrolyte.

[0010] The positive electrode active material according to one or more embodiments can maximize or increase capacity while minimizing or reducing production costs, can ensure long cycle life characteristics and / or can improve high voltage characteristics and high temperature characteristics. When the positive electrode active material is applied to a rechargeable lithium battery, a high initial charge / discharge capacity and initial charge and discharge efficiency can be achieved under relatively high voltage conditions, a long cycle life characteristic can be achieved (or maintained), and the amount of gas generated due to relatively high voltage and relatively high temperature operation can be effectively suppressed or reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] The accompanying drawings are included to provide a further understanding of the present disclosure and are incorporated into and constitute a part of this specification. The accompanying drawings illustrate embodiments of the present disclosure and together with the description serve to explain the principles of the present disclosure. In the accompanying drawings,

[0012] Figure 1 is a diagram schematically illustrating a rechargeable lithium battery according to one or more embodiments.

[0013] Figure 2 and Figure 3 This is a scanning electron microscope (SEM) image of the positive electrode active material of Comparative Example 1.

[0014] Figure 4 and Figure 5 This is a SEM image of the positive electrode active material of Comparative Example 2.

[0015] Figure 6 and Figure 7 This is a SEM image of the positive electrode active material of Example 2.

[0016] Figure 8 and Fig. 9 The SEM-EDS analysis results of the positive electrode active material of Example 2 are shown.

[0017] <Description of Reference Numerals>

[0018] 100: Rechargeable lithium battery 10: Positive electrode

[0019] 20: Negative electrode 30: Separator

[0020] 40: electrode assembly 50: shell DETAILED DESCRIPTION

[0021] Hereinafter, specific embodiments will be described in more detail so that those skilled in the art can easily implement them. However, the present disclosure may be implemented in many different forms and should not be construed as limited to the example embodiments set forth herein.

[0022] The terms used herein are only used to describe the embodiments and are not intended to limit the present disclosure. Unless the context clearly dictates otherwise, a singular expression includes a plural expression.

[0023] As used herein, the term "combination thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of the components.

[0024] In this document, it should be understood that terms such as "comprising", "including" or "having" are intended to indicate the presence of implemented aspects, features, quantities, operations, elements and / or their (e.g., any appropriate) combinations, but they do not exclude the possibility of the presence or addition of one or more other aspects, features, quantities, operations, elements or their (e.g., any appropriate) combinations.

[0025] In the drawings, for the sake of clarity, the thickness of layers, films, panels, regions, etc., is exaggerated, and the same reference numerals represent the same elements throughout, and repeated descriptions thereof may not be provided in the specification. It will be understood that if (for example, when) an element (such as a layer, film, region, or substrate) is referred to as being "on" another element (such as a layer, film, region, or substrate), it may be directly on the other element (such as a layer, film, region, or substrate), or there may also be intervening elements. On the contrary, if (for example, when) an element is referred to as being "directly on" another element, there are no intervening elements.

[0026] In addition, the term "layer" as used herein includes not only a shape formed on the entire surface when viewed from a plan view but also a shape formed on a partial surface.

[0027] In addition, the average particle size can be measured by an appropriate method (e.g., known to those skilled in the art) (e.g., by a particle size analyzer or by a transmission electron microscope image or a scanning electron microscope image). In one or more embodiments, the average particle size value can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles in each particle size range, and calculating therefrom. Unless otherwise specified, the average particle size (D 50 ) may refer to the diameter of particles having a cumulative volume of 50% by volume in a particle size distribution. If (for example, when) no definition is otherwise provided, the average particle size (D) as used herein is 50 ) refers to the diameter of a particle having a cumulative volume of 50% by volume in a particle size distribution obtained by randomly measuring the size (diameter or length of the major axis) of about 20 particles in a scanning electron microscope image.

[0028] In this document, the term "or" is not to be interpreted as an exclusive meaning, for example, "A or B" means A, B, A+B, etc.

[0029] The term "metal" as used herein refers to common metals, transition metals, and metalloids (semimetals).

[0030] Positive electrode active material

[0031] In one or more embodiments, the positive electrode active material includes: core particles (e.g., one core particle) including a lithium nickel manganese aluminum composite oxide (e.g., a plurality of core particles formed by a lithium nickel manganese aluminum composite oxide); and a coating arranged on the surface of the core particles (e.g., each of the) and containing aluminum and yttrium, wherein the nickel content (e.g., nickel in the core particles) is greater than or equal to about 60 mol% based on 100 mol% of the total metals other than lithium in the positive electrode active material, and the aluminum content (e.g., amount) of the coating is about 0.1 mol% to about 2 mol%, and the yttrium content (e.g., amount) of the coating is about 0.05 mol% to about 1 mol%, respectively, based on 100 mol% of the total metals other than lithium in the positive electrode active material.

[0032] Due to the recent sharp rise in the price of rare metal cobalt, it is necessary to develop a positive electrode active material that excludes (does not contain) cobalt or has a reduced cobalt content (e.g., amount). Among them, positive electrode active materials with olivine crystal structure (such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), lithium manganese iron phosphate (LMFP), etc.) or positive electrode active materials with spinel crystal structure (such as lithium manganese oxide (LMO), etc.) are limited in achieving relatively high capacity due to the small amount of available lithium in their structure. Layered nickel-manganese positive electrode active materials have excellent or appropriate capacity and efficiency characteristics due to the relatively high amount of available lithium in the structure, making them suitable as materials for relatively high-capacity batteries. However, as cobalt, which plays a key role in the layered structure, is removed, the structural stability is reduced, the resistance is increased, and it becomes difficult to ensure long cycle life characteristics. In addition, excluding cobalt will cause the side reaction between the positive electrode active material and the electrolyte to accelerate under relatively high voltage and relatively high temperature conditions, thereby increasing the amount of gas generated and deteriorating the cycle life characteristics.

[0033] In one or more embodiments, aluminum is introduced into the base material, and lithium nickel manganese aluminum composite oxide is applied as a core particle to improve structural stability and minimize or reduce production costs. In addition, aluminum and yttrium are coated synchronously (e.g., simultaneously) at appropriate (e.g., specific) contents to form a substantially uniform coating to provide a positive electrode active material that can maximize or increase capacity and efficiency and achieve long cycle life characteristics by reducing gas generation even under relatively high voltage or relatively high temperature conditions.

[0034] Nuclear particles

[0035] The core particles include a lithium nickel manganese aluminum based composite oxide.

[0036] The nickel content (eg, amount) satisfies greater than or equal to about 60 mol % based on 100 mol % of the total metals excluding lithium in the positive electrode active material.

[0037] Nickel is contained in the core particles, but can be moved to some coatings during the coating process. Therefore, nickel content (e.g., amount) can refer to the nickel content (e.g., amount) contained in the entire positive electrode active material (e.g., in both the core and the coating). Based on the total metal other than lithium in the positive electrode active material of 100mol%, the nickel content (e.g., amount) can be, for example, about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If the nickel content (e.g., amount) meets the above range, even if the cobalt content (e.g., amount) is reduced or there is no cobalt, a relatively high capacity can be achieved, and structural stability can be increased.

[0038] In some embodiments, based on 100mol% of the total metal other than lithium in the positive electrode active material, the manganese content (e.g., amount) may be, for example, about 10mol% to about 40mol%, about 10mol% to about 39mol%, about 10mol% to about 35mol%, about 10mol% to about 30mol%, about 10mol% to about 29mol%, about 15mol% to about 39mol%, about 20mol% to about 39mol%, or about 20mol% to about 30%. Manganese is contained in the core particles, but can move to some coatings during the coating process, so the manganese content (e.g., amount) may refer to the manganese content (e.g., amount) contained in the entire positive electrode active material (e.g., in both the core and the coating). If the manganese content (e.g., amount) satisfies the above range, the positive electrode active material can improve structural stability while achieving relatively high capacity.

[0039] Based on 100mol% of the total metals other than lithium in the positive electrode active material, the aluminum content (e.g., amount) of the core particles may be greater than or equal to about 0.1mol%, greater than or equal to about 0.5mol%, or greater than or equal to about 1mol%, for example, about 1mol% to about 3mol%, about 1mol% to about 2.5mol%, about 1mol% to about 2mol%, or about 1mol% to about 1.9mol%. In this article, the aluminum content (e.g., amount) refers to the content (e.g., amount) of aluminum present in the core particles. If the aluminum content (e.g., amount) of the core particles satisfies the above range, even if cobalt is excluded from the core particles, a stable layered structure can be maintained, the problem of structural collapse caused by charging and discharging can be suppressed or reduced, and the long cycle life characteristics of the positive electrode active material can be achieved.

[0040] According to one or more embodiments, the aluminum concentration within the core particle can be substantially uniform. In some embodiments, there may be an aluminum concentration gradient from the center to the surface within the core particle, or the aluminum concentration inside the core particle may be neither higher nor lower than the outside, and the aluminum within the core particle may be uniformly distributed. This may be a structure obtained by using an aluminum raw material during precursor production and not additionally doping aluminum during the synthesis of the core particle, thereby using nickel-manganese-aluminum hydroxide as a precursor to synthesize a composite oxide. The core particle may be in the form of a secondary particle in which a plurality of primary particles are aggregated, and the aluminum content (e.g., amount) inside the primary particle may be the same (or substantially the same) or similar regardless of the position of the primary particle. For example, if a primary particle is selected at a random position in a cross section of a secondary particle, and the aluminum content (e.g., amount) is measured inside the primary particle rather than at its (e.g., with another particle) interface, then regardless of the position of the primary particle, that is, regardless of whether the primary particle is close to the center of the secondary particle or close to the surface of the secondary particle, the aluminum content (e.g., amount) may be (e.g., substantially) the same / similar / uniform. In this structure, even if cobalt is absent or present in a very small amount, a stable layered structure can be maintained and aluminum byproducts or aluminum aggregates are not generated, thereby simultaneously improving the capacity, efficiency, and cycle life characteristics of the positive electrode active material.

[0041] In some embodiments, the lithium nickel manganese aluminum-based composite oxide may be represented by Chemical Formula 1.

[0042] [Chemical formula 1]

[0043] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1

[0044] In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.39, 0.01≤z1≤0.03, 0≤w1≤0.29, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W and Zr, and X is one or more elements selected from F, P and S.

[0045] In some embodiments, in Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5 or 0.9 ≤ a1 ≤ 1.2. In some embodiments, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8 or 0.7 ≤ x1 ≤ 0.79; 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39 or 0.2 ≤ y1 ≤ 0.3; 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02 or 0.01 < z1 ≤ 0.019; and 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1 or 0 ≤ w1 ≤ 0.09.

[0046] In some embodiments, the lithium nickel manganese aluminum-based composite oxide of the core particles may be a cobalt-free compound that does not include cobalt or includes a very small amount of cobalt.

[0047] The core particles may be in the form of secondary particles made by aggregating a plurality of primary particles. The secondary particles may be spherical, oval, polyhedral, irregular in shape, and / or a combination thereof (e.g., any suitable combination), and the primary particles may be spherical, oval, plate-shaped, and / or a combination thereof (e.g., any suitable combination).

[0048] If (e.g., when) the battery operates under conditions of relatively high voltage and / or relatively high temperature, the core particles are vulnerable to chemical erosion by the components in the electrolyte, and side reactions with the electrolyte may occur. Accordingly, there may be problems of reducing the battery cycle life and safety due to the generation of a large amount of gas. These problems can be solved by introducing a coating according to one or more embodiments described in more detail later.

[0049] Coating

[0050] Based on 100 mol% of the total metal other than lithium in the positive electrode active material, the aluminum content (e.g., amount) in the coating may be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%. The Al content (e.g., amount) refers only to the content (e.g., amount) of aluminum included in the coating, and the content (e.g., amount) of aluminum included in the core particles is not included (not calculated). The aluminum content (e.g., amount) in the coating can be measured, for example, by SEM-EDS analysis of the surface or cross-section of the positive electrode active material. If the aluminum content (e.g., amount) in the coating satisfies these ranges, the coating can have a substantially uniform and thin thickness, which may not increase the resistance of the positive electrode active material, while effectively inhibiting or reducing side reactions with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery under relatively high voltage and relatively high temperature conditions. For example, if the aluminum content (e.g., amount) of the coating is too much (e.g., greater than about 2 mol%), a substantially uniform coating may not be formed or resistance may increase, which may reduce initial charge and discharge efficiency and cycle life characteristics, and if the aluminum content (e.g., amount) of the coating is too little (e.g., less than about 0.1 mol%), a coating of a suitable or appropriate thickness may not be formed and the effect of inhibiting or reducing side reactions with the electrolyte may be reduced.

[0051] Based on 100 mol% of the total metals other than lithium in the positive electrode active material, the yttrium content (e.g., amount) in the coating may be about 0.05 mol% to about 1 mol%, such as about 0.1 mol% to about 1 mol%, about 0.1 mol% to about 0.9 mol%, about 0.1 mol% to about 0.8 mol% or about 0.1 mol% to about 0.6 mol%. If the yttrium content (e.g., amount) satisfies the above range, the positive electrode active material forms a good or appropriate coating without reducing capacity or increasing resistance, effectively suppressing or reducing side reactions with the electrolyte, and effectively reducing the amount of gas generated under relatively high voltage or relatively high temperature conditions.

[0052] In one or more embodiments, both aluminum and yttrium are included (e.g., simultaneously) in the coating, and compared to a case where only one of the two is included (e.g., included), the amount of gas generated under relatively high voltage or relatively high temperature operating conditions can be significantly reduced, and the cycle life characteristics can be improved.

[0053] The coating according to one or more embodiments may be in the form of a film that continuously surrounds the surface of the core particle, for example, it may be in the form of a shell that surrounds (e.g., encapsulates) the entire surface of the core particle. This is different from a structure in which only a portion of the surface of the core particle is partially coated. According to one or more embodiments, the coating may be formed to cover the entire surface of the core particle, and may be formed to be very thin or substantially thin and substantially uniform in thickness, so the positive electrode active material does not substantially increase resistance or substantially reduce capacity, while still appropriately improving structural stability, effectively suppressing side reactions with the electrolyte, substantially reducing the amount of gas generated under conditions of relatively high voltage and relatively high temperature, and achieving relatively long cycle life characteristics.

[0054] The thickness of the coating may be about 30 nanometers (nm) to about 500nm, such as about 30nm to about 450nm, about 30nm to about 400nm, about 30nm to about 350nm, about 30nm to about 300nm, about 30nm to about 250nm, about 30nm to about 200nm, about 30nm to about 150nm, about 50nm to about 500nm, about 80nm to about 500nm or about 100nm to about 500nm. If the coating meets the above thickness range, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating, and the side reaction with the electrolyte can be effectively suppressed or reduced. The thickness of the coating can be measured by, for example, TOF-SIMS, XPS or EDS analysis, and the thickness range of the coating can be measured by TEM-EDS line profile.

[0055] The coating according to one or more embodiments may be thin and substantially uniform in thickness, at the level of tens to hundreds of nanometers. For example, the deviation of the coating thickness within a positive electrode active material particle may be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the deviation of the coating thickness refers to the deviation of the coating thickness within a positive electrode active material particle. For example, the deviation of the coating thickness can be calculated by measuring the thickness of about 10 points in the electron microscope image of the cross section of a single positive electrode active material particle to calculate the arithmetic mean, and then the absolute value of the difference between a measured data and the arithmetic mean is divided by the arithmetic mean and multiplied by 100 to calculate. The fact that the deviation or standard deviation of the coating thickness meets the above range indicates that a coating with substantially uniform thickness is formed (e.g., well formed) in the form of a film on the surface of the positive electrode active material particle. Accordingly, the structural stability of the positive electrode active material is improved, the side reaction with the electrolyte is effectively suppressed or reduced, and the resistance increase or capacity reduction caused by the coating can be minimized or reduced.

[0056] Due to the properties of each element in the coating, the aluminum may be present as a substantially continuous film, whereas the yttrium may be present as islands or in separate patterns.

[0057] In one or more embodiments, aluminum and yttrium may be mixed in one coating layer. In this case, aluminum may exist in the form of a substantially continuous film, and yttrium may exist in the form of islands instead, but the present disclosure is not limited thereto.

[0058] In one or more embodiments, aluminum and yttrium may each form a separate layer. For example, the positive electrode active material according to one or more embodiments may include: a first coating layer, disposed on the surface of the core particle and including aluminum; and a second coating layer, disposed on the first coating layer and including yttrium. The first coating layer in the form of a thin film may be formed when aluminum is first attached or absorbed to the surface of the core particle, and then yttrium may be coated thereon to form a second coating layer. In some embodiments, yttrium may be mixed in the first coating layer and the second coating layer, but the first coating layer may be an aluminum-rich coating layer composed mainly of aluminum, and the second coating layer may be a yttrium-rich coating layer composed mainly of yttrium. Also in this case, yttrium may be present in the second coating layer in the form of islands, but the present disclosure is not limited thereto.

[0059] The thickness of the first coating and the second coating is not particularly limited. However, the thickness of the first coating may be about 10nm to about 200nm, such as about 20nm to about 200nm, about 30nm to about 200nm, or about 30nm to about 180nm. The thickness of the second coating may be about 20nm to about 300nm, such as about 20nm to about 250nm, about 20nm to about 200nm, about 30nm to about 300nm, or about 50nm to about 300nm. If each thickness satisfies the above respective ranges, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating, and the amount of gas generated during operation at relatively high voltage and relatively high temperature can be effectively reduced by effectively suppressing or reducing side reactions with the electrolyte.

[0060] In one or more embodiments, in addition to aluminum and yttrium, the coating may further include nickel, manganese or (e.g., any appropriate) combination thereof. The nickel and manganese included in the core particles may be introduced during the coating formation process, and their content is not particularly limited. The coating according to one or more embodiments essentially includes aluminum and yttrium, and optionally includes nickel and manganese, and is formed to be thin and substantially uniform in thickness, thereby improving the relatively high voltage characteristics of the positive electrode active material and improving the cycle life characteristics.

[0061] Grain boundary coating part

[0062] During the coating formation process, aluminum may diffuse into the core particles. Accordingly, the positive electrode active material according to one or more embodiments may further include a grain boundary coating portion on the surface of the primary particle including aluminum and arranged inside the secondary particle. In this article, the secondary particle refers to the core particle, and the interior of the secondary particle may refer to the entire interior except the surface of the secondary particle, or the interior may be a region of about 60% length from the center of the secondary particle toward the surface of the secondary particle to the radius of the secondary particle. The grain boundary coating portion is distinguished from the coating on the surface of the core particle, but refers to the coating portion formed on the surface of the primary particle in the core particle. The presence of the grain boundary coating portion can be confirmed by SEM-EDS analysis of a cross section of the positive electrode active material. By forming (or providing) an aluminum grain boundary coating portion, the positive electrode active material can become more structurally stable and its cycle life characteristics can be improved.

[0063] The aluminum content (eg, amount) in the grain boundary coating portion is not particularly limited, and, for example, the aluminum content (eg, amount) in the grain boundary coating portion may be smaller than the aluminum content (eg, amount) in the coating layer.

[0064] In some embodiments, in addition to aluminum, the grain boundary coating portion may further include nickel, manganese, yttrium, or (eg, any suitable) combination thereof.

[0065] The average particle size (D 50 ) is not particularly limited, but may be, for example, about 10 micrometers (μm) to about 18 μm, about 11 μm to about 16 μm, or about 12 μm to about 15 μm. If the average particle size of the secondary particles of the positive electrode active material satisfies the above range, a relatively high capacity and a long cycle life may be achieved, and it may be suitable (e.g., advantageously) to form a coating according to one or more embodiments.

[0066] The cobalt content (e.g., amount) in the positive electrode active material according to one or more embodiments may be, for example, less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%, such as about 0 mol% to about 0.01 mol%, based on 100 mol% of the total metals other than lithium in the positive electrode active material. The positive electrode active material according to one or more embodiments may be, for example, a cobalt-free positive electrode active material.

[0067] The positive electrode active material according to one or more embodiments may be, for example, a cobalt-free positive electrode active material. Generally speaking, sodium ions may be used in the preparation process of the positive electrode active material, but according to the preparation method described in more detail later, a core particle having a stable structure and a coating having a substantially uniform thickness may be formed without using sodium ions.

[0068] Method for preparing positive electrode active material

[0069] In one or more embodiments, the method for preparing a positive electrode active material includes mixing a layered nickel manganese aluminum composite hydroxide and a lithium raw material and performing a first heat treatment to obtain a lithium nickel manganese aluminum composite oxide, and adding the lithium nickel manganese composite oxide to a solution in which an aluminum raw material and a yttrium raw material are mixed in an aqueous solvent, followed by mixing, drying and performing a second heat treatment to obtain a positive electrode active material. Based on 100 mol% of the total metal in the layered nickel manganese aluminum composite hydroxide, the nickel content (e.g., amount) in the layered nickel manganese aluminum composite hydroxide is greater than or equal to about 60 mol%, based on 100 mol% of the total metal other than lithium in the positive electrode active material, the aluminum content (e.g., amount) of the aluminum raw material is about 0.1 mol% to about 2 mol%, and based on 100 mol% of the total metal other than lithium in the positive electrode active material, the yttrium content (e.g., amount) of the yttrium raw material is about 0.05 mol% to about 1 mol%. The aforementioned positive electrode active material can be prepared by the aforementioned method.

[0070] The layered nickel-manganese-aluminum composite hydroxide as a precursor of the core particles may be in the form of secondary particles in which a plurality of primary particles are aggregated, and may not contain cobalt or may contain a very small amount of cobalt. For example, it may be a cobalt-free layered nickel-manganese-aluminum composite hydroxide. The layered nickel-manganese-aluminum composite hydroxide may be prepared by an appropriate (e.g., general) coprecipitation method.

[0071] The method for preparing a positive electrode active material according to one or more embodiments does not include additional doping with aluminum when preparing core particles, but uses an aluminum raw material when preparing a precursor, thereby using a nickel-manganese-aluminum composite hydroxide in which aluminum is uniformly dispersed in the structure as a precursor. Such a precursor can be used to prepare a positive electrode active material as follows: the positive electrode active material can stably maintain a layered structure despite repeated charging and discharging without the presence of cobalt, wherein no aluminum byproduct or aluminum aggregate is formed, thereby improving the capacity and efficiency characteristics and cycle life characteristics of the positive electrode active material.

[0072] Based on 100mol% of the total metal in the nickel-manganese-aluminum composite hydroxide, the nickel content (e.g., amount) in the nickel-manganese-aluminum composite hydroxide may be greater than or equal to about 60mol%, such as about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If the nickel content (e.g., amount) satisfies the above range, even if the cobalt content (e.g., amount) is reduced or there is no cobalt, a relatively high capacity can be achieved, and structural stability can be increased.

[0073] Based on 100 mol% of the total metals in the nickel-manganese-aluminum composite hydroxide, the manganese content (e.g., amount) in the nickel-manganese-aluminum composite hydroxide may be 10 mol% to about 40 mol%, about 10 mol% to about 39 mol%, about 10 mol% to about 35 mol%, about 10 mol% to about 30 mol%, about 10 mol% to about 29 mol%, about 15 mol% to about 39 mol%, about 20 mol% to about 39 mol%, or about 20 mol% to about 30 mol%. In addition, based on 100 mol% of the total metals in the nickel-manganese-aluminum composite hydroxide, the aluminum content (e.g., amount) in the nickel-manganese-aluminum composite hydroxide may be greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, such as about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 1.9 mol%. If the manganese content and the aluminum content of the composite hydroxide satisfy the above ranges, a relatively high capacity can be achieved, while the structural stability of the positive electrode active material can be increased, and the production price can be reduced to increase economic benefits.

[0074] Based on 100 mol% of the total metals in the nickel-manganese-aluminum composite hydroxide, the cobalt content (e.g., amount) in the nickel-manganese-aluminum composite hydroxide may be less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%. The nickel-manganese-aluminum composite hydroxide can be said to be economical because it avoids or reduces the increase in unit cost caused by cobalt, maximizes or increases capacity, and improves structural stability.

[0075] In some embodiments, the nickel-manganese-aluminum-based composite hydroxide may be represented by Chemical Formula 2.

[0076] [Chemical formula 2]

[0077] Ni x2 Mn y2 Al z2 M 2 w2 (OH)2

[0078] In Chemical Formula 2, 0.6≤x2≤0.8, 0.1≤y2≤0.39, 0.01≤z2≤0.03, 0≤w2≤0.29, and 0.9≤x2+y2+z2+w2≤1.1, and M 2 It is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W and Zr.

[0079] The nickel-manganese-aluminum composite hydroxide is in the form of particles, and the average particle size (D50 ) may be about 10 μm to about 18 μm, about 11 μm to about 16 μm, or about 12 μm to about 15 μm.

[0080] The nickel-manganese-based composite hydroxide and the lithium raw material may be mixed in a molar ratio of about 1:0.9 to about 1:1.8 (eg, about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2).

[0081] The first heat treatment may be performed in an oxygen atmosphere, for example, at a temperature range of about 750° C. to about 950° C., about 780° C. to about 900° C., or about 810° C. to about 890° C. for about 2 hours to about 20 hours or about 4 hours to about 12 hours.

[0082] By the first heat treatment, a lithium nickel manganese aluminum composite oxide can be obtained. Based on 100 mol% of the total metals other than lithium in the lithium nickel manganese aluminum composite oxide, the obtained lithium nickel manganese aluminum composite oxide may include greater than or equal to about 60 mol% (e.g., about 60 mol% to about 80 mol%) of nickel, but may not include cobalt or include cobalt in a very small amount of less than or equal to about 0.01 mol% based on 100 mol% of the total metals other than lithium in the lithium nickel manganese aluminum composite oxide. The lithium nickel manganese aluminum composite oxide has a residual lithium content (e.g., amount) and different surface characteristics that are significantly different from oxides having other components (e.g., other oxides) (e.g., nickel oxides of the prior art (such as lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, etc.)). The coating method of the prior art may not be able to form (or provide) a good or appropriate coating thereon in the form of a substantially uniform film. In one or more embodiments, a method is provided for improving relatively high voltage characteristics by uniformly (substantially uniformly) forming (or providing) a coating having a very thin thickness on the surface of a lithium nickel manganese aluminum composite oxide having a very small amount of cobalt and a nickel content (e.g., amount) greater than or equal to about 60 mol %.

[0083] In one or more embodiments, the lithium nickel manganese aluminum composite oxide obtained by the first heat treatment is added to a solution in which an aluminum raw material and a yttrium raw material are mixed in an aqueous solvent, followed by mixing, drying, and a second heat treatment to obtain a coating according to one or more embodiments. This coating method may be referred to as a wet coating method.

[0084] The aqueous solvent may include distilled water, an alcohol solvent, or a combination thereof (e.g., any appropriate). The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof (e.g., any appropriate). For example, the aluminum raw material may include aluminum sulfate, and in this case, it is suitable (e.g., advantageously) to form a coating having a substantially uniform thickness on the surface of the lithium nickel manganese composite oxide particles. For example, the yttrium raw material may include yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide, or a combination thereof (e.g., any appropriate).

[0085] The aluminum raw material is a raw material for forming (or providing) a coating layer, and the aluminum content (e.g., amount) from the aluminum raw material can be designed to be about 0.1 mol% to about 2 mol%, for example, about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%, based on 100 mol% of the total metals other than lithium in the finally obtained positive electrode active material. Similarly, the yttrium raw material is a raw material for forming (or providing) a coating layer, and the yttrium content (e.g., amount) from the yttrium raw material can be designed to be about 0.05 mol% to about 1 mol%, for example, about 0.1 mol% to about 1 mol%, about 0.1 mol% to about 0.9 mol%, about 0.1 mol% to about 0.8 mol%, or about 0.1 mol% to about 0.6 mol%, based on 100 mol% of the total metals other than lithium in the finally obtained positive electrode active material. If the content of the coating raw material is designed to have a corresponding range, the coating can be formed to have a thin and substantially uniform thickness of tens or hundreds of nanometers, which can reduce the amount of gas generated in rechargeable lithium batteries under relatively high voltage or relatively high temperature operating conditions and improve relatively high capacity and long cycle life characteristics.

[0086] The solution obtained by mixing the aluminum raw material and the yttrium raw material in an aqueous solvent may have a pH of about 1.5 to about 3.5 (e.g., about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2). The lithium nickel manganese aluminum composite oxide is dripped (added) to the solution in which the aluminum raw material and the yttrium raw material are mixed in an aqueous solvent and mixed for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 40 minutes. After stirring (mixing), the mixed solution may have a pH of about 4.5 to about 8.5 (e.g., about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0). If these conditions are met, it is suitable (e.g., advantageously) to form a coating having a substantially uniform thickness.

[0087] Drying after the mixing process may be understood as a process of removing the solvent, and may be performed, for example, at about 40°C to about 240°C, about 100°C to about 220°C, or about 150°C to about 200°C.

[0088] The second heat treatment can be understood as a process for forming (or providing) a coating, and can be performed, for example, in an oxygen atmosphere at a temperature range of about 700°C to about 850°C, about 750°C to about 840°C, or about 800°C to about 830°C for about 2 hours to about 20 hours or about 3 hours to about 10 hours. In addition, the second heat treatment temperature can be lower than the first heat treatment temperature, and the second heat treatment time can be the same as the first heat treatment time or shorter than the first heat treatment time. A desired or appropriate coating can be obtained by performing a second heat treatment under these conditions.

[0089] Positive electrode

[0090] In one or more embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material. In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include other types (kinds) of positive electrode active materials. In addition, the positive electrode active material layer may optionally further include a binder, a conductive material, or a combination thereof (e.g., any appropriate).

[0091] According to one or more embodiments, the loading level of the positive electrode active material layer may be about 10 mg / cm 2 ~ about 40mg / cm 2 , for example about 10 mg / cm 2 ~about 30mg / cm 2 or about 10 mg / cm 2 ~about 20mg / cm 2 . In addition, the density of the positive electrode active material layer in the final compressed positive electrode may be about 3.3 g / cc to about 3.7 g / cc, for example, about 3.3 g / cc to about 3.6 g / cc or about 3.4 g / cc to about 3.58 g / cc. When the positive electrode active material according to one or more embodiments is applied, such a load level and density of the positive electrode active material layer may be expected or advantageously achieved, and a positive electrode satisfying the load level and density of the positive electrode active material layer within the above range is suitable for achieving a relatively high capacity, relatively high energy density rechargeable lithium battery.

[0092] Binder

[0093] The binder improves the bonding properties between the positive electrode active material particles and between the positive electrode active material particles and the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin or nylon, but the present disclosure is not limited thereto.

[0094] Conductive Materials

[0095] A conductive material (e.g., an electronic conductor) is included to provide electrode conductivity, and any suitable conductive material may be used as the conductive material unless it causes a chemical change. Examples of the conductive material may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials such as metal powder or metal fiber including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or (e.g., any suitable) mixtures thereof.

[0096] Each content (eg, amount) of the binder and the conductive material may be about 0.5 wt % to about 5 wt % based on about 100 wt % of the positive electrode active material layer.

[0097] The positive electrode current collector may include Al, but the present disclosure is not limited thereto.

[0098] Rechargeable lithium battery

[0099] According to some embodiments, a rechargeable lithium battery includes the aforementioned positive electrode, negative electrode, and electrolyte.

[0100] According to the shape, the rechargeable lithium batteries can be classified into cylindrical, prismatic, pouch, coin, etc. Figure 1 Schematic diagram showing a rechargeable lithium battery according to one or more embodiments. Figure 1 , the rechargeable lithium battery 100 includes: an electrode assembly 40 manufactured by winding a separator 30 interposed between a positive electrode 10 and a negative electrode 20; and a case 50 accommodating therein the electrode assembly 40. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown).

[0101] The rechargeable lithium battery according to one or more embodiments may be rechargeable at a relatively high voltage, or may be suitable for driving at a high relative voltage. For example, the charging voltage of the rechargeable lithium battery may be greater than or equal to about 4.45V, about 4.45V to about 4.7V, about 4.45V to about 4.6V, or about 4.45V to about 4.55V. By applying the positive electrode active material according to one or more embodiments, the rechargeable lithium battery can significantly reduce the amount of gas generated even (for example, when) charging at a relatively high voltage, and can achieve relatively high capacity and long cycle life characteristics.

[0102] Negative electrode

[0103] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector and including a negative electrode active material, and the negative electrode active material layer may further include a binder, a conductive material, and / or (eg, any appropriate) combination thereof.

[0104] Negative electrode active material

[0105] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.

[0106] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, or (for example, any appropriate) combination thereof as a carbonaceous negative electrode active material. Crystalline carbon may be natural graphite or artificial graphite in an amorphous or flaky, flake-like, spherical or fibrous (for example, in the form of fibers). Amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, etc.

[0107] Lithium metal alloys include alloys of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0108] The material capable of being doped / undoped with lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x(0<x≤2), Si-Q alloy (wherein Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements and / or (e.g., any suitable) combination thereof, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po or (e.g., any suitable) combination thereof) or (e.g., any suitable) combination thereof. The Sn-based negative electrode active material may be Sn, SnO x (0<x≤2, for example, SnO2), Sn alloy or their (for example, any suitable) combination.

[0109] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D 50 ) may be, for example, about 0.5 μm to about 20 μm. According to one or more embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, it may include secondary particles (cores) in which silicon primary particles are assembled and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon may also be present between silicon primary particles, for example, silicon primary particles may be coated with amorphous carbon. Secondary particles may be dispersed in an amorphous carbon matrix.

[0110] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core including crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof (e.g., any suitable combination). The amorphous carbon may include soft carbon, hard carbon, mesophase pitch carbonization products, calcined coke, etc.

[0111] If (for example, when) the silicon-carbon composite includes silicon and amorphous carbon, the silicon content (for example, amount) may be about 10 wt% to about 50 wt% and the amorphous carbon content (for example, amount) may be about 50 wt% to about 90 wt% based on about 100 wt% of the silicon-carbon composite. In one or more embodiments, if (for example, when) the silicon-carbon composite includes silicon, amorphous carbon and crystalline carbon, the silicon content (for example, amount) may be about 10 wt% to about 50 wt%, the crystalline carbon content (for example, amount) may be about 10 wt% to about 70 wt%, and the amorphous carbon content (for example, amount) may be about 20 wt% to about 40 wt% based on about 100 wt% of the silicon-carbon composite.

[0112] In some embodiments, the thickness of the amorphous carbon coating layer may be about 5 nm to about 100 nm. The average particle size (D 50 ) may be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may exist as silicon alone, in the form of a silicon alloy, or in an oxidized form (the silicon particles may exist as silicon alone, in the form of a silicon alloy, or in an oxidized form). The oxidized form of silicon may be SiO x (0<x≤2) represents. At this time, the atomic content (e.g., amount) ratio of Si:O (which indicates the degree of oxidation) may be about 99:1 to about 33:67. If (e.g., when) no definition is provided otherwise, the average particle size (D) as used herein is 50 ) indicates the diameter of particles where the cumulative volume in the particle size distribution is about 50 volume %.

[0113] The Si-based negative electrode active material or the Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. If (for example, when) the Si-based negative electrode active material or the Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed and used, the mixing ratio may be about 1:99 to about 90:10 by weight.

[0114] Binder

[0115] The binder is used to bind the negative electrode active material particles to each other (well bind), and also to bind the negative electrode active material to the negative electrode current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof (eg, any appropriate one).

[0116] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or (eg, any suitable) combination thereof.

[0117] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenol resin, epoxy resin, polyvinyl alcohol or (e.g., any suitable) combination thereof.

[0118] If (for example, when) an aqueous binder is used as a binder in the negative electrode active material layer, a cellulose compound capable of imparting viscosity may be further included. As the cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and alkali metal salts thereof may be mixed and used. The alkali metal may be Na, K or Li.

[0119] The dry binder may be a polymer material capable of fiberization (eg, in the form of fibers), and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or (eg, any appropriate) combination thereof.

[0120] Conductive Materials

[0121] A conductive material (e.g., an electronic conductor) is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials such as metal powder or metal fiber including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or (e.g., any appropriate) mixtures thereof.

[0122] The content (e.g., amount) of the negative electrode active material may be about 95 wt% to about 99.5 wt% based on about 100 wt% of the negative electrode active material layer, and the content (e.g., amount) of the binder may be about 0.5 wt% to about 5 wt% based on about 100 wt% of the negative electrode active material layer. For example, the negative electrode active material layer may include about 90 wt% to about 99 wt% of the negative electrode active material, about 0.5 wt% to about 5 wt% of the binder, and about 0.5 wt% to about 5 wt% of the conductive material.

[0123] current collector

[0124] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof, and may be in the form of foil, sheet or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 7 μm to about 10 μm.

[0125] Electrolyte

[0126] An electrolyte for a rechargeable lithium battery may include a non-aqueous organic solvent and a lithium salt.

[0127] The non-aqueous organic solvent is used as a medium for conveying (e.g., transporting) ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent may include a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, an aprotic solvent, or a combination thereof (e.g., any suitable combination).

[0128] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In one or more embodiments, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles (such as R-CN (wherein R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, and may include a double bond, an aromatic ring or an ether bond, etc.)); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane, etc.); cyclopentane sulfone, etc.

[0129] The non-aqueous organic solvent may be used alone or in a mixture of two or more types (kinds), and if (for example, when) two or more types (kinds) are used in a mixed form, the mixing ratio may be suitably or appropriately adjusted according to the desired or appropriate battery performance, which is well known to those skilled in the art.

[0130] If (for example, when) a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.

[0131] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate-based solvent and an aromatic hydrocarbon organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1 and used.

[0132] The electrolyte may further include vinyl ethylene carbonate, vinylene carbonate or ethylene carbonate-based compounds to improve the battery cycle life.

[0133] Examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0134] The lithium salt dissolved in the non-aqueous organic solvent supplies lithium ions in the battery, ensures the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are each independently an integer of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB) and lithium bis(oxalato)borate (LiBOB).

[0135] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. If the concentration of the lithium salt is within the above range, the electrolyte has suitable or appropriate ion conductivity and viscosity, and thus excellent or appropriate performance may be achieved, and lithium ions may be efficiently moved.

[0136] Diaphragm

[0137] Depending on the type or kind of the rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, or a multilayer film of two or more layers thereof (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).

[0138] The membrane may include a porous substrate and a coating located on a surface of the porous substrate (e.g., on one surface or both surfaces or on one side or both sides (e.g., on opposite surfaces or on opposite sides)) and including an organic material, an inorganic material, or a combination thereof (e.g., any suitable one).

[0139] The porous substrate may be a polymer film formed of any one of a polymer selected from polyolefins (such as polyethylene and / or polypropylene), polyesters (such as polyethylene terephthalate and / or polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyether ketones, polyaryletherketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fibers, and polytetrafluoroethylene (e.g., Teflon), or may be a polymer film formed of a copolymer or mixture of two or more thereof.

[0140] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.

[0141] The organic material may include a (meth)acryl-based copolymer, which includes: a first structural unit derived from (meth)acrylamide; and a second structural unit, including at least one of a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid or its salt.

[0142] The inorganic material may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, or (e.g., any suitable) combination thereof, but the present disclosure is not limited thereto. The average particle size (D 50 ) may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.

[0143] An organic material and an inorganic material may be mixed in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.

[0144] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.

[0145] The embodiments and comparative examples of the present disclosure are described in more detail. However, the following examples are merely examples of the present disclosure, and the present disclosure is not limited to the following examples.

[0146] Example 1

[0147] 1. Preparation of positive electrode active material

[0148] Ni 0.75 Mn 0.24 Al 0.01 (OH)2 and LiOH were mixed in a molar ratio of 1:1 and then preliminarily heat-treated at 850°C in an oxygen atmosphere for 8 hours to prepare a composite oxide in the form of secondary particles having LiNi 0.75 Mn 0.24 Al 0.01 O2 composition and an average particle size of about 14 μm (D 50 ).

[0149] After aluminum sulfate and yttrium nitrate were mixed with distilled water as a solvent, LiNi was added thereto. 0.75Mn 0.24 Al 0.01 O2 composite oxide, then mixed for 20 minutes to 60 minutes. In this article, based on 100mol% of the total metals other than lithium in the final positive electrode active material, the aluminum content (e.g., amount) from aluminum sulfate is designed to be 1.0mol%, and based on 100mol% of the total metals other than lithium in the final positive electrode active material, the yttrium content (e.g., amount) from yttrium nitrate is designed to be 0.1mol%. After removing the solvent from the mixed solution, the residue is dried at 190°C, and then secondary heat treated at 825°C in an oxygen atmosphere for 8 hours to obtain the final positive electrode active material.

[0150] 2. Manufacturing of rechargeable lithium battery cells

[0151] 98.5 wt% of the positive electrode active material, 1.0 wt% of the polyvinylidene fluoride binder and 0.5 wt% of the carbon nanotube conductive material were mixed to prepare a positive electrode active material layer slurry, and the slurry was coated on an aluminum foil current collector, then dried and pressed to manufacture a positive electrode. At this time, the loading level of the positive electrode active material layer was 10 mg / cm 2 , and the density of the positive electrode active material layer in the final pressed positive electrode was about 3.4 g / cc.

[0152] 97.5wt% of graphite negative electrode active material, 1.5wt% of carboxymethyl cellulose and 1wt% of styrene-butadiene rubber were mixed in an aqueous solvent to prepare a negative electrode active material layer slurry. The negative electrode active material layer slurry was coated on a copper foil current collector, then dried and pressed to manufacture a negative electrode.

[0153] A rechargeable lithium battery cell was manufactured in a conventional method using a polytetrafluoroethylene separator and using an electrolyte prepared by dissolving 1M LiPF6 in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7.

[0154] Example 2

[0155] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the yttrium content (eg, amount) from yttrium nitrate was designed to be 0.2 mol % based on 100 mol % of total metals other than lithium in the final positive electrode active material.

[0156] Example 3

[0157] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the yttrium content (eg, amount) from yttrium nitrate was designed to be 0.5 mol % based on 100 mol % of total metals other than lithium in the final positive electrode active material.

[0158] Comparative Example 1

[0159] In addition to using LiNi without aluminum and yttrium coating 0.75 Mn 0.24 Al 0.01 A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1 except that a composite oxide of O2 was used as the positive electrode active material.

[0160] Comparative Example 2

[0161] In addition to the addition of LiNi 0.75 Mn 0.24 Al 0.01 The positive electrode active material and the rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the composite oxide of O2 and aluminum sulfate were added to a distilled water solvent (without adding yttrium nitrate (e.g., without containing yttrium nitrate)) to perform aluminum coating alone to prepare the positive electrode active material.

[0162] Comparative Example 3

[0163] In addition to the addition of LiNi 0.75 Mn 0.24 Al 0.01 The positive electrode active material and the rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 2, except that a composite oxide of O2 and yttrium nitrate were added to a distilled water solvent (without adding aluminum sulfate (e.g., without containing aluminum sulfate)) to perform yttrium coating alone to prepare the positive electrode active material.

[0164] Comparative Example 4

[0165] In addition to the addition of LiNi 0.75 Mn 0.24 Al 0.01 The positive electrode active material and the rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 3, except that a composite oxide of O2 and yttrium nitrate were added to a distilled water solvent (without adding aluminum sulfate (e.g., without containing aluminum sulfate)) to perform yttrium coating alone to prepare the positive electrode active material.

[0166] For better understanding, coating designs of the positive electrode active materials of Examples 1 to 3 and Comparative Examples 1 to 4 are shown in Table 1.

[0167] Evaluation Example 1: Surface Analysis of Positive Electrode Active Material

[0168] The positive electrode active materials of Example 2, Comparative Example 1 and Comparative Example 2 were imaged using a scanning electron microscope (SEM). Figure 2 and Figure 3 To show a SEM image of the particle surface of the positive electrode active material having no coating layer according to Comparative Example 1, Figure 4 and Figure 5 To show a SEM image of the particle surface of the positive electrode active material having an aluminum coating alone (without yttrium) according to Comparative Example 2, Figure 6 and Figure 7 : is a SEM image showing the particle surface of the positive electrode active material according to Example 2. Figure 2 to Figure 7 As a result, the positive electrode active material of Example 2 has a surface shape (eg, morphology) different from those of Comparative Examples 1 and 2.

[0169] in addition, Figure 8 and Fig. 9 This is a SEM-EDS analysis image of a cross section of the positive electrode active material of Example 2. Figure 8 and Fig. 9 , on the surface of the positive electrode active material of Example 2, a coating layer containing Al and Y was uniformly (substantially uniformly) formed.

[0170] Evaluation Example 2: Evaluation of initial charge / discharge capacity and initial charge and discharge efficiency

[0171] The rechargeable lithium battery cells according to Examples 1 to 3 and Comparative Examples 1 to 4 were each charged at 0.2C constant current to an upper limit voltage of 4.45V and constant voltage charged to 0.05C at 25°C, and then discharged at 0.2C to a cutoff voltage of 3.0V as initial charge and discharge. Table 1 shows the initial charge capacity, initial discharge capacity, and the ratio of the initial discharge capacity to the initial charge capacity as initial charge and discharge efficiency.

[0172] Evaluation Example 3: High Temperature Cycle Life Characteristics

[0173] After the initial charge and discharge of Evaluation Example 2, each battery cell was repeatedly charged and discharged 50 times at 1.0C in the voltage range of 3.0V to 4.45V at 45°C to calculate the ratio of the discharge capacity at the 50th cycle to the initial discharge capacity as the 50th capacity retention rate, and the results are shown in Table 1.

[0174] Evaluation Example 4: Evaluation of the amount of gas generated

[0175] The battery cells of Examples 1 to 3 and Comparative Examples 1 to 4 were initially charged at 4.45 V as in Evaluation Example 2 and stored at 90° C. for 4 hours to measure the amount of generated gas, and the results are shown in Table 1.

[0176] Table 1

[0177]

[0178] Referring to Table 1, the rechargeable lithium battery cells of Examples 1 to 3 each achieved higher or equal initial charge and discharge efficiencies than the rechargeable lithium battery cells of the comparative examples, and also exhibited improved high temperature cycle life characteristics and reduced gas generation under relatively high voltage and relatively high temperature conditions. Under relatively high voltage and relatively high temperature conditions, Comparative Example 1 without a coating exhibited poor high temperature life cycle characteristics and high gas generation, and Comparative Example 2 having an aluminum coating alone, and Comparative Examples 3 and 4 having yttrium coatings alone each exhibited higher gas generation than the examples.

[0179] When describing embodiments of the present inventive concepts, the use of “may” refers to “one or more embodiments of the present inventive concepts”.

[0180] The term "about" and similar terms as used herein are used as terms of approximation and not as terms of degree, and are intended to account for the inherent deviations in measured or calculated values ​​that one of ordinary skill in the art will recognize. "About" as used herein includes the stated value and means within the acceptable range of deviations of the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" may mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the stated value.

[0181] Furthermore, any numerical range set forth herein is intended to include all subranges of the same numerical precision included in the range set forth. For example, the range of "1.0 to 10.0" is intended to include all subranges (and end values) between the minimum value 1.0 set forth and the maximum value 10.0 set forth, that is, a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as, for example, 2.4 to 7.6. Any maximum numerical limit set forth herein is intended to include all lower numerical limits contained therein, and any minimum numerical limit set forth in this specification is intended to include all higher numerical limits contained therein. Accordingly, the applicant reserves the right to modify this specification (including claims) to explicitly set forth any subranges contained in the range explicitly set forth herein.

[0182] Unless otherwise defined, in the present disclosure, if (e.g., when) the particles are spherical, the term "particle size" refers to the average diameter, and if (e.g., when) the particles are non-spherical, the term "particle size" refers to the average major axis length.

[0183] The battery management system (BMS) device and / or any other related device or component according to the embodiments of the present invention described herein may be implemented using any appropriate hardware, firmware (e.g., a dedicated integrated circuit), software, or a combination of software, firmware, and hardware. For example, the various components of the device may be formed on an integrated circuit (IC) chip or on a separate IC chip. In addition, the various components of the device may be implemented on a flexible printed circuit film, a tape carrier package (TCP), or a printed circuit board (PCB), or formed on a substrate. In addition, the various components of the device may be processes or threads running on one or more processors in one or more computing devices, executing computer program instructions and interacting with other system components to perform the various functions described herein. The computer program instructions are stored in a memory, which may be implemented in a computing device using a standard memory device, such as, for example, a random access memory (RAM). The computer program instructions may also be stored in other non-temporary computer-readable media (such as, for example, a CD-ROM, a flash drive, etc.). Moreover, those skilled in the art should recognize that, without departing from the scope of the present disclosure, the functions of various computing devices may be combined or integrated into a single computing device, or the functions of a dedicated computing device may be distributed on one or more other computing devices.

[0184] While the disclosure has been described in connection with what are presently considered to be practical example embodiments, it is to be understood that the disclosure is not limited to the disclosed embodiments, but on the contrary, is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the claims and equivalents thereof.

Claims

1. A positive electrode active material comprising: Core particles, including lithium nickel manganese aluminum composite oxide; and a coating layer located on the surface of the core particle and containing aluminum and yttrium, in The amount of nickel in the core particles is greater than or equal to 60 mol%, based on 100 mol% of the total metals other than lithium in the positive electrode active material. The amount of aluminum in the coating layer is 0.1 mol% to 2 mol% based on 100 mol% of the total metals except lithium in the positive electrode active material, and The amount of yttrium in the coating layer is 0.05 mol% to 1 mol% based on 100 mol% of the total metals except lithium in the positive electrode active material.

2. The positive electrode active material according to claim 1, wherein The amount of aluminum in the coating layer is 0.5 mol% to 1.5 mol% based on 100 mol% of the total metals except lithium in the positive electrode active material, and The amount of yttrium in the coating layer is 0.1 mol% to 0.8 mol% based on 100 mol% of the total metals except lithium in the positive electrode active material. 3 . The positive electrode active material according to claim 1 , wherein the coating layer is in the form of a shell continuously surrounding the surface of the core particle. 4 . The positive electrode active material according to claim 1 , wherein the coating layer has a thickness of 30 nm to 500 nm. 5 . The positive electrode active material according to claim 1 , wherein a deviation in thickness of the coating layer is less than or equal to 20%.

6. The positive electrode active material according to claim 1, wherein aluminum exists in the coating layer in the form of a continuous film, and yttrium exists in the coating layer in the form of islands.

7. The positive electrode active material as claimed in claim 1, wherein aluminum and yttrium are mixed in the coating layer.

8. The positive electrode active material according to claim 1, wherein the positive electrode active material comprises: a first coating layer, located on the surface of the core particle and comprising aluminum, and A second coating is disposed on the first coating and includes yttrium.

9. The positive electrode active material according to claim 8, wherein: The thickness of the first coating is 10nm to 200nm, and The thickness of the second coating layer is 20nm-300nm.

10. The positive electrode active material of claim 1, wherein the coating layer further contains nickel, manganese or a combination thereof. 11 . The positive electrode active material of claim 1 , wherein the amount of nickel in the core particles is 60 mol % to 80 mol % based on 100 mol % of the total metals excluding lithium in the positive electrode active material. 12 . The positive electrode active material of claim 1 , wherein the amount of aluminum in the core particles is 1 mol % to 3 mol % based on 100 mol % of the total metals excluding lithium in the positive electrode active material.

13. The positive electrode active material according to claim 1, wherein the lithium nickel manganese aluminum composite oxide of the core particle is represented by Chemical Formula 1: Chemical formula 1 Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1 Wherein in Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.39, 0.01≤z1≤0.03, 0≤w1≤0.29, 0.9≤x1+y1+z1+w1≤1.1 and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W and Zr, and X is one or more elements selected from F, P and S. 14 . The positive electrode active material of claim 1 , wherein the amount of cobalt is 0 mol % to 0.01 mol % based on 100 mol % of the total metals except lithium in the positive electrode active material. 15 . The positive electrode active material according to claim 1 , wherein the lithium nickel manganese aluminum-based composite oxide of the core particle is a cobalt-free compound. 16 . The positive electrode active material according to claim 1 , wherein the core particle is in the form of a secondary particle made by aggregating a plurality of primary particles. 17 . The positive electrode active material of claim 16 , further comprising a grain boundary coating portion located on the surface of the primary particle inside the secondary particle and including aluminum. 18 . The positive electrode active material of claim 17 , wherein the grain boundary coating portion further comprises nickel, manganese, yttrium, or a combination thereof.

19. The positive electrode active material of claim 17, wherein the amount of aluminum in the grain boundary coating portion is smaller than the amount of aluminum in the coating layer.

20. The positive electrode active material according to claim 1, wherein the average particle size D of the positive electrode active material in the form of particles is 50It is 10μm~18μm.

21. The positive electrode active material of claim 1, wherein the positive electrode active material does not contain sodium.

22. A method for preparing a positive electrode active material, the method comprising: The nickel-manganese-aluminum composite hydroxide and the lithium raw material are mixed and subjected to a first heat treatment to obtain a lithium-nickel-manganese-aluminum composite oxide, and adding the lithium nickel manganese aluminum composite oxide to a solution in which an aluminum raw material and a yttrium raw material are mixed in an aqueous solvent, followed by mixing, drying and performing a second heat treatment to obtain a positive electrode active material, in Based on 100 mol % of the total metals in the nickel-manganese-aluminum composite hydroxide, the amount of nickel in the nickel-manganese-aluminum composite hydroxide is greater than or equal to 60 mol %. The amount of aluminum from the aluminum raw material is 0.1 mol% to 2 mol% based on 100 mol% of the total metals except lithium in the positive electrode active material, and The amount of yttrium from the yttrium raw material is 0.05 mol% to 1 mol% based on 100 mol% of total metals except lithium in the positive electrode active material.

23. The method of claim 22, wherein: The amount of aluminum from the aluminum raw material is 0.5 mol% to 1.5 mol% based on 100 mol% of the total metals except lithium in the positive electrode active material, and The amount of yttrium from the yttrium raw material is 0.1 mol% to 0.8 mol% based on 100 mol% of total metals except lithium in the positive electrode active material.

24. The method of claim 22, wherein: The aluminum raw material includes aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide or a combination thereof, and The yttrium raw material includes yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide or a combination thereof.

25. The method of claim 22, wherein the solution in which the aluminum raw material and the yttrium raw material are mixed in the aqueous solvent has a pH of 1.5 to 3.

5.

26. The method of claim 22, wherein: The first heat treatment is performed at 750°C to 950°C, and The second heat treatment is performed at 700°C to 850°C.

27. The method of claim 22, wherein: The nickel-manganese-aluminum composite hydroxide has 60 mol% to 80 mol% of nickel based on 100 mol% of total metals in the nickel-manganese-aluminum composite hydroxide, and The nickel-manganese-aluminum-based composite hydroxide has 1 mol% to 3 mol% of aluminum based on 100 mol% of total metals in the nickel-manganese-aluminum-based composite hydroxide.

28. A positive electrode comprising: positive electrode current collector; and a positive electrode active material layer on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 21 or a positive electrode active material prepared by the method for preparing a positive electrode active material according to any one of claims 22 to 27.

29. The positive electrode of claim 28, wherein the loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 .

30. The positive electrode of claim 28, wherein the positive electrode active material layer has a density of 3.3 g / cc to 3.7 g / cc.

31. A rechargeable lithium battery comprising: The positive electrode according to any one of claims 28 to 30, negative electrode, and Electrolyte.

32. The rechargeable lithium battery of claim 31, wherein the charging voltage is greater than or equal to 4.45V.